Bacillus cereus in Packaging Material: Molecular and Phenotypical Diversity Revealed - Schmid, Paul Jakob; Maitz, Stephanie; Kittinger, Clemens (Frontiers in Microbiology, 2021)
The Bacillus cereus group has been isolated from soils, water, plants and numerous food products. These species can produce a variety of toxins including several enterotoxins (Nhe, Hbl, CytK, EntFM), the emetic toxin cereulide and insecticidal Bt toxins. This is the first study evaluating the presence of B. cereus in packaging material. Among 75 different isolates, four phylogenetic groups were detected (II, III, IV, VI), of which the groups III and IV were the most abundant with 46.7% and 41.3%, respectively. One isolate was affiliated to psychrotolerant group VI. Growth experiments showed a mesophilic predominance. Based on PCR analysis, nhe genes were detectable in 100% of the isolates, while hbl genes were only found in 50.7%. The cereulide encoding gene was found in four out of 75 isolates, no isolate carried a crystal toxin gene. In total, thirteen different toxin gene profiles were identified. We showed that a variety of B. cereus group strains can be found in packaging material. Here, this variety lies in the presence of four phylogenetic groups, thirteen toxin gene profiles and different growth temperatures. The results suggest that packaging material does not contain significant amounts of highly virulent strains, and the low number of cereulide producing strains is in accordance with other results.